A influência de sonic youth na contracultura dos anos 1990 - (:unkn) unknown (Universidade Federal do Pampa, 2023)
This work aims to discuss the influence of the American band Sonic Youth on the counterculture of the 1990s. To achieve this goal, the study explores bibliographic research to explain the concept of alternative rock, review the history of Sonic Youth, investigate the notion of counterculture, and explore the landscape of the 1990s. To elucidate the band's influence, it employs folk communication, selecting elements that constitute the band and discussing the identified influence in materials containing representations with noticeable impacts from Sonic Youth. The work establishes the following characteristic elements of the band: Sound, Behavior and attitudes, Kim Gordon's legacy, and Aesthetics - Design and Clothing. It chooses the following materials for discussion: two albums, an advertising piece, the riot grrrl movement, three concert posters, and clothing style. Finally, the study analyzes the influence within these materials to determine whether Sonic Youth has an influence on the counterculture of the 1990s or not.
Keywords: Influência musical; Contracultura; Bandas (Música); Sonic Youth; Anos 1990; Rock alternativo; Counterculture; Musical influence; CNPQ::CIENCIAS SOCIAIS APLICADAS